تيسير الدرس النحوي ونقده عند محمود الطناحي - المالكي، عبيد بن أحمد بن عبيد (جامعة الباحة, 2024)
يتناول هذا البحث القضايا التي عرض لها الطناحي في مؤلفاته وتحقيقاته ومقالاته تحت عنوان: تيسير الدرس النحوي ونقده عند محمود الطناحي، وتأتي أهميته من جِدَّتِه، وإلقائه الضوء على الاتجاه النحوي لمحقق من طراز رفيع، راميًا بذلك إلى رسم صورة كاملة للاتجاه العام للطناحي فيما جد في الدرس النحوي؛ كقضية تيسير النحو، ونقد الفكر النحوي، وتناول النحو في ضوء المناهج الحديثة في علم اللغة، وأيضًا عرض أفكاره عن أزمة العربية وأسبابها وسبيل الخروج منها، وقد اعتمد البحث على المنهج الوصفي التحليلي؛ لعرض القضايا ومناقشتها، والمنهج المقارن؛ لإبراز أوجه الاتفاق والتباين بين اتجاه الطناحي واتجاه غيره من المحدثين، وانتهت الورقة إلى أن تيسير النحو ظهر قديما في المختصرات والمنظومات، واتجه إليه المحدثون طرائق قددًا؛ فمنهم المحافظ كالطناحي، الذي يرى ضرورة العودة للكتاب القديم، ومنهم المجدد بتغيير الأصول، أو إلغاء بعض الأبواب والمصطلحات، أو إخضاع النحو للمناهج الحديثة، هذا، وقد أدت هيمنة تلك المناهج على الدرس النحوي إلى ابتعاد أبناء العربية عن تراثهم، وتبدت آثار ذلك في التدني الذي وصل إليه خريجو كليات اللغة العربية؛ لذا فقد أوصت الورقة بعمل مشروع ضخم تشرف عليه الهيئات والمجامع اللغوية، يعيد بناء الهيكل النحوي، مستفيدا من المناهج اللغوية قديمها وحديثها، متكئا في ذلك على النص القرآني؛ ليصل عموم الأمة به، وأوصت أيضًا بأن يكون تعليم العربية مناسبًا للغرض من كل مرحلة تعليمية؛ فالمرحلة قبل الجامعية تركز على قواعد ضبط اللسان، والمرحلة الجامعية تركز على قدرة الخريجين على تدريس العربية بصورة سليمة، ومرحلة الدراسات العليا تنفذ بالطالب إلى أعماق اللغة ليصبح قادرا على الإضافة إليها. This research addresses the issues to which Al-Tanahi presented his publications, investigations and articles under the title: The Issues of Facilitating and Criticizing Grammar by Mahmoud Al-Tanahi. Its importance originates from the fact that it is new, and the fact that it sheds light on the grammatical direction of a top-tier scholar. In doing so, this research aims to draw a complete picture of the general direction of Al-Tanahi in regard to the trends of grammar study, such as the issue of facilitating grammar, criticism of grammatical thought and addressing grammar in the light of contemporary linguistic approaches. It also presents Al-Tanahi’s ideas regarding the Arabic language crisis, its causes, and the way out of it. This paper makes use of the descriptive analytical method to present and discuss issues, and the comparative approach to highlight the similarities and differences between the direction of Al-Tanahi and that of other contemporary scholars. It concludes that the facilitation of grammar first appeared in the past in abbreviations and systems, and that contemporary scholars addressed it in different ways; some of them, such as Al-Tanahi, approached it in a conservative manner, emphasizing the need to return to the old book, whereas others advocated the renewal of origins, cancelation of some elements and terms or subjecting grammar to modern approaches. The dominance of such approaches on the study of grammar has led the Arabic speaking nations to distance from their heritage, and the effects of this are observed in the decline of graduates of Arabic language faculties. Thus, this paper recommends the establishment of a huge project supervised by linguistic bodies and academies, which rebuilds the grammatical structure, taking advantage of old and contemporary linguistic approaches and leaning on the Qur’anic text, to reach the whole nation. In addition, this paper recommends that the teaching of Arabic be suitable for each educational stage; the pre-university stage focusing on students’ ability to adjust their tongues according to the Arabic language rules, the undergraduate stage focusing on the ability of graduates to teach Arabic properly, and the postgraduate stage taking students to the depths of the language to be able to add onto it.
Keywords: اللغة العربية -- النحو العربي -- المناهج اللغوية -- البناء النحوي